Search for resonant pair production of Higgs bosons in the bb[bar]bb[bar] final state using pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2022)
A search for resonant Higgs boson pair production in the b¯bb¯b final state is presented. The analysis uses 126 fb−1-139 fb−1 of pp collision data at √s=13 TeV collected with the ATLAS detector at the Large Hadron Collider. The analysis is divided into two channels, targeting Higgs boson decays which are reconstructed as pairs of small-radius jets or as individual large-radius jets. Spin-0 and spin-2 benchmark signal models are considered, both of which correspond to resonant HH production via gluon-gluon fusion. The data are consistent with Standard Model predictions. Upper limits are set on the production cross section times branching ratio to Higgs boson pairs of a new resonance in the mass range from 251 GeV to 5 TeV.
Im Titel steht der 2. und 4. Buchstabe "b" mit einem Oberstrich
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
*ATLAS Collaboration: G. Aad, F. Bartels, F.L. Castillo, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, A. Krishnan, T.Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, T.M. Spieker, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, X. Yue, J. Zinsser [und 2897 weitere Personen]
Gesehen am 25.07.2022